2018
DOI: 10.21511/bbs.13(2).2018.03
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the efficiency performance of Sharia and conventional banks using stochastic frontier analysis

Abstract: There are two sectors of banks operating in Indonesia, namely Sharia banks and conventional banks. Improving performance is important in maintaining public confidence in the bank. Efficiency is one of the parameters to measure the performance of Sharia banks. This study measures the comparative level of technical efficiency of Sharia commercial banks and conventional banks by Stochastic Frontier Analysis method during 2011–2015 period by using 10 samples of Sharia commercial banks and conventional banks. Input… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 18 publications
1
15
1
1
Order By: Relevance
“…At this time many banking companies have built risk management in their companies in an effort to reduce the risk that will occur as a result of lending activities undertaken. To cover the cost of funds, good risk management can help companies avoid as much as possible the costs that must be incurred (Sadalia, 2018). High level of competition among all banks, and the rapid development of the internal and external environment of the bank, the slogan of the principle of "Prudential Banking" was apparently still not able to minimize the losses experienced by banks due to errors in operations and the provision of problem loans whose granting system was influenced by many factors.…”
Section: Introductionmentioning
confidence: 99%
“…At this time many banking companies have built risk management in their companies in an effort to reduce the risk that will occur as a result of lending activities undertaken. To cover the cost of funds, good risk management can help companies avoid as much as possible the costs that must be incurred (Sadalia, 2018). High level of competition among all banks, and the rapid development of the internal and external environment of the bank, the slogan of the principle of "Prudential Banking" was apparently still not able to minimize the losses experienced by banks due to errors in operations and the provision of problem loans whose granting system was influenced by many factors.…”
Section: Introductionmentioning
confidence: 99%
“…The coefficient of determination (R²) essentially measures the extent of the model's ability to explain the variables of dependent variables Suriadi et al, 2015;Syahyunan et al, 2017;Sirojuzilam et al, 2017;Sihombing et al, 2017;Tarmizi et al, 2016Tarmizi et al, , 2017Yahya et al, 2017;Sari et al, 2018;Sadalia et al, 2018;Eriadi et al, 2018;.…”
Section: Determination Coefficient Analysis (R²)mentioning
confidence: 99%
“…Studies on bank efficiency in Indonesia have so far been dominated by commercial banks in general and have tended to focus more on the level of bank efficiency without further examining the determinants of that level of efficiency (Hadad et al 2012;Hadad et al 2003a;Kurnia 2004;Muharam 2007;Ferari & Sudarsono 2011;Omar et al 2007;Kalis et al 2012;Pramuka 2011;Sadalia & Kautsar 2018). Using Data Envelopment Analysis (DEA), Omar et al (2007) stated that in 2004, the level of technical efficiency of commercial banks in Indonesia, for both conventional and Sharia banks, was still low, at 86 percent.…”
Section: Introductionmentioning
confidence: 99%
“…Pramuka (2011) used the DEA approach to assess the efficiency of Islamic banks and found that bank efficiency levels tended to increase from 2003 to 2009, from 88 percent to 99 percent. On the other hand, Sadalia and Kautsar (2018) used the Stochastic Frontier Analysis (SFA) approach to assess the level of technical efficiency of banks in Indonesia and found that conventional and Islamic commercial banks in Indonesia were inefficient, with an efficiency rate of 84 percent for conventional banks and 85 percent for Islamic banks. Wardhani and Mongid (2019) focused on assessing the efficiency of Islamic banks in Indonesia using the SFA approach and found the level of efficiency of Islamic banks to be in the low and medium range.…”
Section: Introductionmentioning
confidence: 99%